Theileria cervi in Amblyomma neumanni (Acari: Ixodida, Ixodidae) collected on horses from North-western Argentina - Montini, Martina (2025)
Amblyomma neumanni ticks collected on horses from the North-West of Argentina were analyzed for the presence of the Piroplasm agents Babesia and Theileria. A total of 97 adult ticks from four different provinces (Jujuy, Santiago del Estero, Salta, Tucumán) were included in this study. Genomic DNA was isolated, and conventional PCR assays were applied for the detection of the 18S rDNA gene of Babesia and Theileria species. One sample corresponding to a male of A. neumanni collected in Tapia, Tucumán Province, resulted positive. Phylogenetic analyses carried out with the obtained 18S rDNA partial gene sequences resulted in the identification of Theileria cervi. Although the detection of T. cervi in A. neumanni collected on a horse does not represent direct evidence of its vector competence regarding this Theileria species, it can be seen as an indication of the circulation of T. cervi in the epidemiological circuit formed by the interaction A. neumanni-horses.